FUNGSI PAJIDOR DALAM PESTA PA’BUNTINGANG - Achmad Maulana (SELONDING, 2019)
Pajidor is a musical art performance that uses flutes, jidor, and ropolo (drums or tambourines). As one of the traditional types of Makassar ethnic music, pajidor has quite an important function in community activities as evidenced by its frequent use in pa’buntingang. Based on this phenomenon, the focus of the research is to describe the function of pajidor in the pa’buntingang.This study uses qualitative methods sourced from library research, interviews, observations, documentation, which is equipped with data analysis.This research shows that pajidor is a musical performance art at pa'buntingang event with a function as a means of entertainment and aesthetic pleasure.